GPS methodology for cadastral surveying and mapping in Albania - Barnes, Grenville; Chaplin, Bruce; Moyer, D. David (Land Tenure Center, University of Wisconsin-Madison, 1998)
This paper is a compilation of three reports written over the 1993-96 period in the development and testing of a cadastral surveying and mapping methodology to support land registration. The sections cover (1) fieldwork to evaluate options for cadastral surveying and mapping in Albania, (2) the results on defining and testing methodology utilizing Global Positioning System (GPS) technology and on the costs and benefits of various surveying and mapping options, and (3) further testing in 1995 of the newly developed GPS methodology.
vi, 106 p.
Keywords: Global Positioning System; Artificial satellites in surveying Albania; Cadastres Albania; Surveying Albania; Land administration Albania